Itsar (Altruism) in Zakat in the Community of Pagar Alam City, South Sumatra - Melis; Riska Dwi Septiani; Muharir; Nova Yanti Maleha; Choirunnisak (CV. Era Digital Nusantara, 2026)
This study aims to examine the influence of altruism on zakat payment decisions among the community of Pagar Alam City, South Sumatra. The method used in this study is quantitative. The population in this study were community in Dempo Makmur Village who work as coffee plantation farmers. The sample was taken from a portion of the Muslim community living in Dempo Makmur Village. The method used for sampling was Purposive Sampling, a non-random sampling method where researchers select individuals or groups based on certain criteria relevant to the research objectives. The technique used to collect data in this study was a questionnaire. The results of the study indicate that altruism has a significant influence on the decision to pay zakat on coffee plantations among the community of Dempo Makmur Village, North Pagar Alam District.